2010
DOI: 10.1021/es902946j
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Source Water Quality on Multiwall Carbon Nanotube Coagulation

Abstract: Potable water treatment facilities may become an important barrier in limiting human exposure to engineered nanoparticles (ENPs) as ENPs begin to contaminate natural aquatic systems. Coagulation of ENPs will likely be a major process that controls the ENP fate and the subsequent removal in the aqueous phase. The influence that source water quality has on ENP coagulation is still relatively unknown. The current study uses a 2(3) x 2(4-1) fractional factorial design to identify seven key surface water constituen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…Removal of Cu up to 95% was achieved at the OD of coagulant Al 2 O 3 /L (Figure 3). These results suggest a dependency of CuO NPs removal on the source water characteristics and dosage of applied coagulant as demonstrated in earlier studies [21,22]. The results in Figure 3 further show the key role of DOM characteristics on the coagulant dose and overall performance of the coagulation process.…”
Section: Removal Of Cuo Npssupporting
confidence: 81%
See 1 more Smart Citation
“…Removal of Cu up to 95% was achieved at the OD of coagulant Al 2 O 3 /L (Figure 3). These results suggest a dependency of CuO NPs removal on the source water characteristics and dosage of applied coagulant as demonstrated in earlier studies [21,22]. The results in Figure 3 further show the key role of DOM characteristics on the coagulant dose and overall performance of the coagulation process.…”
Section: Removal Of Cuo Npssupporting
confidence: 81%
“…The high removal of CuO NPs in these conditions may also be attributed to the presence of metal cations (K + , Mg 2+ ). Holbrook et al demonstrated that the specific adsorption of divalent cation increased the NPs agglomeration at a wide range of pH levels in a complex environment [22].…”
Section: Agglomeration Of Cuo Npsmentioning
confidence: 99%
“…The life cycle of many NPs is expected to include their release into wastewater treatment plants as a primary route through which they might ultimately enter the environment [6][7][8]. The potential for different steps in the wastewater treatment plant to remove CNPs, therefore, has also been investigated [18][19][20]. Based on the likely scenarios for CNPs to arrive in the environment, it is possible to indicate the types of ecosystems likely to be contaminated and the organisms that are of highest priority for testing the negative effects of CNPs (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Coagulation is an efficient and simple process commonly used in water treatment to remove suspended solids, organic and inorganic substances from the water. Earlier studies [17][18][19] reported that NPs including cadmium telluride (CdTe), C(60), and multiwall carbon nanotubes (MWCNT) were efficiently removed from water by alum as well as polyaluminum chloride (PACl) coagulation. In addition, variable coagulation efficiencies of different ENPs, such as Ag (2-21%), ZnO (46-98%) and TiO 2 (2-9%) have also been reported [20].…”
Section: Introductionmentioning
confidence: 99%